PENGEMBANGAN KURIKULUM DAN METODE PEMBELAJARAN DI TPA AL-HIDAYAH DESA TUMPUK KABUPATEN PONOROGO - Umi Isnatin; Jaudat Iqbal Harris; Lalu Ananta; Amru Saputra; Firmana Putra (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2024)
This study aims to develop curriculum and learning methods at TPA Al-Hidayah, Tumpuk Village, Ponorogo Regency, as an effort to improve the quality of religious education and the Qur'an for children. Through the Thematic Real Work Lecture (KKNT) program from Darussalam Gontor University, we collaborate with TPA Al-Hidayah to design a more structured and relevant curriculum and apply innovative and interesting learning methods for TPA students. We conduct observation, curriculum development, learning implementation, and evaluation to evaluate the effectiveness of the learning methods applied. As a result, we found significant improvements in the ability to read the Qur'an and understanding Islamic religious teachings in TPA students. These steps underscore the importance of developing curricula and learning methods that suit students' needs to improve the quality of religious education in TPA.